Estimation of arsenic in nail using silver diethyldithiocarbamate method - Habiba Akhter Bhuiyan; Kipchu Tshering; Mir Misbahuddin (Bangladesh Pharmacological Society, 2015)
Spectrophotometric method of arsenic estimation in nails has four steps: a) washing of nails, b) digestion of nails, c) arsenic generation, and finally d) reading absorbance using spectrophotometer. Although the method is a cheapest one, widely used and effective, it is time consuming, laborious and need caution while using four acids.   Video Clips Nail wash:                 3.2 min Digestion of nail:        7.0 min Arsine generation:     10.0 min Reading absorbance:   1.2 min